A characterisation of amyloid status and cognition in late‐life depression: Neuropsychology/Neuropsychological correlates of physiologic markers of cognitive decline/Dementia. (7th December 2020) - Golemme, Mara; Loreto, Flavia; Patel, Neva; Win, Zarni; Tam, Henry; Sadiq, Dilman; Nijran, Kuldip; Malhotra, Paresh A.; Perry, Richard J.
Abstract: Background: The link between late‐life depression and Alzheimer's disease (AD) has long been investigated, however it is still unclear whether depression acts as a risk factor, a prodromal feature or a comorbid condition in AD. Clarifying the nature of this link has important implications in the early intervention and diagnosis of AD. The relatively recent introduction of in‐vivo brain biomarkers for AD pathology offers the chance to explore the relationship between depression and pathologically‐confirmed neurodegeneration. Here, we examined the association among objective cognitive functioning, self‐reported cognitive failures and AD pathology in patients with late‐life depression. Method: Sixty‐three older adults with no formal diagnosis of cognitive impairment underwent a comprehensive cognitive assessment and Amyloid‐PET Imaging at the Imperial Memory Unit. Participants were classified into two groups, according to the presence (n=33, mean age=71.82 ±4.98) or absence (n=30, mean age=71.30 ±5.80) of late‐life depression. Late‐life depression was confirmed through validated questionnaires (GDS ≥ 6 and/or HDRS ≥ 12) and medical history review. Amyloid‐PET images were qualitatively read as amyloid positive or amyloid negative by two experienced nuclear medicine radiologists (NMRs). Equivocal scans (6%) were read by a third independent NMR. Cognitive data in the two groups were compared using non‐parametric tests. Results: Amyloid status did not differ significantly between the two groups (p=.367), with 3 (9%) depressed and 5 (17%) non‐depressed participants reported as amyloid‐positive. Despite higher levels of self‐reported cognitive failures (p<.001), the depressed group did not differ from the non‐depressed group in a global measure of cognition (MMSE depressed: 28.09±1.69; non‐depressed: 28.93±4.66) and showed worse performance in 4 (Word List short‐delay recall, Digit Span backward and forward, Coding) of the 17 cognitive measures administered. Follow up data, currently being collected at our Unit, will add information about the long‐term trajectory of cognition in late life depression. Conclusions: In our sample, depressive symptoms were associated with a limited number of cognitive measures but not with AD pathology. This suggests that depression seems to have a limited role in the early diagnosis of AD. Future studies should examine the role of specific features of depression and of other widespread neuropsychiatric symptoms (e.g., anxiety) in AD.